Pengaruh Jumlah Wajib Pajak, Luas Lahan, Jumlah Bangunan, Dan Laju Inflasi Terhadap Penerimaan Pajak Bumi Dan Bangunan (PBB) - Afriyanah Afriyanah; Waluyo Waluyo (Universitas Multimedia Nusantara, 2015)
The purpose of this study was to examine the effect of the total taxpayers, land area, the total of buildings, and inflation rate for land and building tax (PBB). In this study, the total taxpayers is measured by the number of taxpayers based on Surat Tanda Terima Setoran, land area and the number of buildings based on the Surat Pemberitahuan Pajak Terutang, and the rate of inflation based on the Consumer Price Index for expenditure group.The object of this research is the receipt of PBB in each district in the city of Tangerang from period 2010 to 2013. The sample was selected using all of the population as a sample and secondary data used in this study were analyzed using multiple regression method. In total there are 13 districts in the city of Tangerang observed by the researcher.The results of this study are the total of taxpayers, land area, and the total of buildings individually have a significant influence on the receipt of PBB, while the result for inflation rate is not significant. The total of taxpayers, land area, total of buildings, and inflation rate have significant influence on the receipt of PBB simultaneously. Keywords: Inflation rate, Land and Building Tax (PBB) revenues, land area, total of buildings, total taxpayers.